Rossification and Creolization: the Influence of External Factors on the Development of the Ukrainian Language - Пясецький, Петро Ярославович; Рудник, Олег (Науково-дослідний інститут українознавства Київського національного університету імені Тараса Шевченка, 2026)
Relevance of the research. This work is primarily based on the personal scientific project of P. J. Piaseckyj, a Ukrainian diaspora scholar from the USA. It was the project titled "Anglo Surzhyk," which was initiated on February 9, 2018 (and still ongoing), that provided the author with the further impetus to write this paper. The project itself is a study of the prevalence of Anglicisms in everyday, academic, cultural, and professional Ukrainian communication. It is based on articles from Ukrainian media published on the Internet and currently contains over 2,500 borrowings. The project is continuously updated and thus not available in print; an electronic copy may be requested directly from the author via email or by visiting its namesake Facebook page. [2] The author began contemplating the Anglicization of the Ukrainian language as early as 1949, at the age of six, upon arriving in New York and hearing the Anglicized Ukrainian spoken by American Ukrainians (from the first and second waves of emigration). Mr. Piaseckyj himself is fully proficient in English and possesses a "keen sensibility toward our language." On the other hand, Oleh Rudnyk (who is also fully proficient in both mentioned languages) focuses this work on the linguistic purism movement, specifically its historical continuity and its relevance to societal needs within the context of contemporary Ukrainian national realities. This focus is grounded in the ideas and works of American researchers such as Edward Sapir, Benjamin Lee Whorf, and Welsh scholar Rhianwen Daniel [23, 24, 25]. This work also serves as an appeal to the Ukrainian academic community to more urgently address the issue of protecting the Ukrainian language from the phenomenon of creolization in the current conditions of global advancement. The purpose of this work is to analyze the historical preconditions and current manifestations of linguistic distortion—caused by Rossification and the influx of mediated Anglicisms—to fully comprehend this influx. We investigate the consequences of these phenomena for the development of the lexical richness and word-formation capacity of the Ukrainian language. Concurrently, we advocate for the necessity of implementing effective measures for its protection. These conclusions are grounded in the empirical analysis of a corpus of words, gathered within the framework of the “Anglo Surzhyk” project [2], which attests to the Rossian-mediated provenance of a considerable portion of these borrowings. Emphasis is placed on the essential role of governmental involvement in the defense and standardization of the Ukrainian language amid globalization and persistent external influence. Conclusions. The cumulative effect of centuries of Rossification, coupled with the percolation of Anglicisms mediated through the Russian language, poses a considerable threat to the evolution of modern Ukrainian. This pervasive process risks the language's creolization and the potential erosion of its distinct identity. Notwithstanding the substantial lexical richness of the Ukrainian vocabulary, there exists an urgent necessity for proactive measures aimed at linguistic protection and norming. The establishment of a specialized state ministry, such as a Ministry for Language Purity—modeled after the French system—is a pivotal step to ensuring the oversight of linguistic standards, the development of specialized terminology, and the preservation of Ukrainian's uniqueness amid global challenges. Furthermore, it is essential to recover and republish dictionaries dating from the 1920’s from archives, universities, libraries, private collections, and even the Security Service of Ukraine (SBU). Ultimately, the defense of the language is not merely a linguistic pursuit but a national priority that underpins cultural and state identity.

Актуальність. Робота базується в основному на особистому науковому проєкті українського діаспорянина-науковця зі США П. Я. Пясецького. Саме проєкт «Анґло Суржик», початий 9 лютого 2018 р. (є незавершеним досі), дав автору поштовх до написання цієї праці. Дослідження поширеності англіцизмів в українському повсякденному, науковому, культурному та професійному мовленні, ґрунтуючись на статтях українських ЗМІ, оприлюднених в Інтернеті, на цей час містить уже понад 2500 запозичень. Проєкт постійно оновлюється, тому не є друкованим. Автор почав застановлятися над питанням англіфікації української мови ще у віці 6 років (1949), коли приїхав до Нью-Йорка та почув українську англіфіковану мову з уст американських українців (першої та другої хвиль еміграції). Сам П. Пясецький прекрасно володіє англійською та має «тонке відчуття до нашої мови». З другого боку, Олег Рудник у дослідженні зосереджує увагу на русі за чистоту мови (linguistic purism), зокрема у змісті його історичної тяглості та відповідності суспільним потребам щодо сьогоднішньої української дійсності, ґрунтуючись на доробках західних дослідників, таких як Едвард Сепір, Бенджамін Лі Ворф та Ріанвен Деніел. Ця праця також несе характер відозви до українських наукових кіл для стрімкішого порушення питання про захист української мови від явища креолізації в сучасних умовах глобалізаційного поступу. Метою дослідження є аналіз історичних передумов та сучасних проявів мовного викривлення, спричиненого росифікацією та напливом опосередкованих англіцизмів, щоб зрозуміти цей поступ. Висновки. Вплив багатовікової росифікації, а також опосередкованих англіцизмів, що проникають через російську мову, є значною загрозою для розвитку сучасної української мови. Цей процес призводить до її креолізації та можливої втрати самобутності. Попри значне лексичне багатство українського словника існує нагальна потреба в активних заходах для захисту та унормування мови. Створення спеціалізованого державного міністерства, такого як Міністерство чистоти державної мови, за прикладом Франції, є ключовим кроком для забезпечення контролю за мовними нормами, розвитку термінології та збереження унікальності української мови в умовах глобалізаційних викликів. Є потреба віднайти в архівах, університетах, бібліотеках, особисто в громаді та Службі безпеки України (СБУ) словники з 1920-х років і перевидати їх. Захист мови – це не лише мовне, а й національне питання, що є основою культурної та державної тотожності.
Pосифікація та креолізація: вплив зовнішніх чинників на розвиток української мови
Keywords: rossification; rossisms; anglicisms; empirical analysis; Ukrainian language; language policy; korenizatsiia; linguistics; surzhyk; creolization; росифікація; росизми; англіцизми; англізми; емпіричний аналіз; українська мова; мовна політика; мовознавство; суржик; креолізація